BACTERIAL SENSITIVITY TEST KLEBSIELLA SPP. ISOLATED FROM KINTAMANI DOG DIARRHEA AGAINST ANTIBIOTICS - Ananta Kusuma, Anak Agung Gede Agung; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2023)
This study aims to determine the pattern of sensitivity of bacteria Klebsiella spp. isolated from kintamani dogs with diarrhea. The sample of this study were 4 isolates of Klebsiella spp. isolated from kintamani dogs with diarrhea. The method used in this study is the Kirby-Bauer disc diffusion method in duplicate using the antibiotics Kanamycin , Sulfamethoxazole-trimethoprim, and Streptomycin . The data obtained were expressed descriptively qualitatively by measuring the antibiotic inhibition zone formed. The results showed that isolates of  Klebsiella spp. 75% intermediate (3 isolates) and 25%(1 isolate) sensitive to Kanamycin , all samples sensitive to Sulfamethoxazole-trimethoprim and 75% (3 isolates) sample intermediate and 25% (1 isolate) sensitive to  Streptomycin .